Occurrence of arbuscular mycorrhizal fungi after organic fertilization in maize, cowpea and cotton intercropping systems=Ocorrência de fungos micorrízicos arbusculares após adubação orgânica em sistemas consorciados de milho, feijão e algodão - Marlon da Silva Garrido; Leonor Costa Maia; Fritz Oehl; Everardo Valadares de Sá Barreto Sampaio; Rômulo Simões Cezar Menezes; Carla da Silva Sousa; Francisco de Sousa Lima (Acta Scientiarum: Agronomy, 2012)
The effect of organic manure on the community of mycorrhizal fungi (AMF) was evaluated in maize, cowpea and cotton intercropping systems in a semi-arid region of Brazil over two consecutive years. The experiment was conducted using a randomized block design with four replicates and six soil treatments: (M) goat manure incorporated in the soil before planting; (G) gliricidia prunings incorporated before planting; (M+G) manure and gliricidia incorporated before planting; (GS) gliricidia applied on the soil surface 45 days after planting; (M+GS) manure incorporated before planting and gliricidia applied to the surface 45 days after planting; and (C) control treatment without incorporation. It was not possible to identify the best treatment for both years in terms of spore density, mycorrhizal colonization and glomalin content. However, there was a significant effect from the fertilization treatments when compared to the control in most treatments. In both years, M+GS favored glomalin and AMF sporulation in the cotton plots. In the second year, which had low rainfall, there was an increase in production of spores, glomalin, colonization and AMF species richness irrespective of soil incorporation and culture. Plots that were fertilized with manure presented greater AMF species richness regardless of the year and crop type. O efeito da adubação orgânica sobre a comunidade de fungos micorrízicos arbusculares (FMA) em sistemas consorciados com milho, feijão e algodão foi avaliado no semi-árido paraibano, ao longo de dois anos. O experimento foi conduzido em delineamento de blocos casualizados com quatro repetições e seis tratamentos: (M) esterco incorporado no solo antes do plantio; (G) ramas de gliricídia incorporadas antes do plantio; (M+G) esterco e gliricídia incorporados no solo antes do plantio; (GS) gliricídia aplicada em cobertura 45 dias após o plantio; (M+GS) esterco incorporado antes do plantio e gliricídia aplicada em cobertura 45 dias após o plantio; (C) tratamento controle. Não foi possível identificar um melhor tratamento, em ambos os anos, em termos de densidade de esporos, colonização micorrízica e teor de glomalina. Entretanto, houve efeito significativo das incorporações na maioria dos tratamentos quando comparados ao controle. Em ambos os anos, M+GS favoreceu a produção de glomalina e a esporulação de FMA no sistema com algodoeiro. No segundo ano, de poucas chuvas, houve aumentos na produção de esporos, glomalina, colonização e riqueza de espécies de FMA, independentemente do efeito das incorporações e da cultura. Os tratamentos com esterco apresentaram maior riqueza de espécies, independentemente do ano e da cultura.